BAKTI SOSIAL TELEDENTISTRY KEDOKTERAN GIGI, SUATU ALTERNATIF BAGI MASYARAKAT PADA MASA PANDEMI COVID-19 - Haria Fitri; Suci Rahma Sari; Nila Kasuma; Rahmi Khairani; Dedi Sumantri (LPPM (Institute for Research and Community Services) Universitas Andalas Padang, 2021)
Teledentistry is an examination and consultation of patients to the dentist without going through face-to-face visits, but with the help of an online application. The purpose of the activity is to help and facilitate Co-ass students of the Faculty of Dentistry, Andalas University, to fulfill the requirements for oral diagnosis via online (teledentistry) during the covid 19 pandemic. The activity is carried out in the form of examination/screening of patients carried out by Co-ass students whom Hospital Precept accompanies at the Faculty of Dentistry, Andalas University (Lecturer). Activities to be carried out consist of counseling, coordinator, mentoring, and monitoring of implementation and evaluation. The results of this activity can meet the patient's need for dental and oral examinations and expand access to dental care. Dental and oral health is essential for every individual, especially for carrying out functions such as eating, speaking, aesthetics, and feeling comfortable throughout the day. The Covid-19 pandemic limits the community's social conditions, including their need to get dental and oral services from dentists. In addition, dentistry is one of the jobs most at risk of contracting Covid-19 from patients. Through teledentistry activities, a dentist takes anamnesis to patients, clinical examinations are carried out through consultation through pictures and videos, diagnosis as initial information in planning further treatment, and supportive care such as patient education.